Islam's Compromise With Archipelago Culture in The Islamic Boarding School and Madrasah Education System in Indonesia (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2025)
This study examines the dynamics of accommodation and compromise between Islamic values and Nusantara cultural traditions in the context of the development of pesantren and madrasah educational systems in Indonesia. Historically, the spread of Islam in the Nusantara archipelago did not occur confrontationally, but rather through a long process of cultural negotiation, giving birth to a distinctive model of Islamic education different from Islamic educational traditions elsewhere in the world. Using a social history approach, this research traces how pesantren and madrasah grew as educational institutions that not only transferred religious doctrine, but also became spaces of synthesis between classical Islamic scholarly traditions and local Nusantara wisdom. The results show that the Islam-Nusantara compromise in the pesantren and madrasah educational system is reflected in three main aspects: (1) adaptation of teaching methods combining the halaqah tradition with Nusantara oral culture; (2) integration of customary values and local ethics into the akhlak and tasawuf curriculum; and (3) institutional flexibility of pesantren in responding to social change without abandoning its Islamic identity.
Keywords: Islam Nusantara; pesantren; madrasah; cultural acculturation; social history of education; Islamic education; Islamic kingdoms